Kvantiteetti ja aika I. Nominaalisen aspektin näkökulma suomen objektin ja subjektin sijamerkintään - Huumo, Tuomas (Virittäjä, 2006)
Quantity and time I: Nominal aspect and the case marking of subject and object in Finnish (englanti) 4/2006 (110) Quantity and time I: Nominal aspect and the case marking of subject and object in Finnish The article examines how nominal aspect motivates the case marking of the (existential) subject and object in Finnish. Nominal aspect refers to the aspectual interpretation of a sentence based on the nature of the participation of a nominal referent in an event. In general, the referent of a nominal element can either participate in the situation as a whole, i.e. from beginning to end, as in John was patting the dog, or in an incremental way, where different components of the referent participate in the event in a sequence, as in John was mowing the lawn. In the incremental type the activity proceeds not only in time but also in relation to the referent of the object (the lawn), such that the portion of the referent already affected by the activity gradually increases until the activity has covered the whole referent and reaches its endpoint. In earlier research it has been shown that case variation between the partitive object and the so-called total object (morphologically marked with the accusative, nominative or genitive case) is based either on quantification of the event alone or on both quantification of the event and the existence of a nominal referent that participates in the event incrementally. In general, the partitive object indicates irresultativity, i.e. that the situation is aspectually unbounded (for instance atelic or progressive aspect), whereas the total object indicates resultativity, i.e. that the situation is aspectually bounded. Typically, the total object refers to a situation where an accomplishment has been brought to its conclusion. The writer argues that there is also another type of nominal aspect used in conjunction with verbal aspect, namely the use of the total object in aspectually unbounded sentences. This type consists of expressions such as Ole+n jo kauan osta+nut shk+n t+lt yhti+lt [have+present.1.singular already long.time buy+ participle electricity+genitive(total) this+ablative company+ablative] I have bought / been buying my electricity from this company for ages already. This example indicates a homogeneous relationship where the person is continuously buying electricity from a particular company. As the situation is aspectually unbounded, the quantity of electricity must also be unbounded, i.e. there is no temporal or quantitative boundary to the purchasing of electricity. What motivates use of the total object here is the additional meaning that the person is continuously buying all his/her electricity from this particular company. If the partitive object were used, the meaning would change and leave open the possibility that electricity is being purchased from other sources too. The relevant quantitative distinction between the two types of object is thus based on boundedness vs. unboundedness of the quantity at each individual point of time during the event. This opposition can be broadly paraphrased by saying that the total object conveys the meaning continuously all and the partitive object the meaning continuously some. To clarify this opposition the writer draws a distinction between static and dynamic quantity. Static quantity is the quantity of a nominal referent at each individual point of time during the event, whereas dynamic quantity is incremental and accumulates with time. The writer argues that it is often the bounded static quantity of a nominal referent that invokes the use of the total object in sentences that are aspectually unbounded. It is also shown that there is an aspectual parallel to this quantitative opposition that motivates use of the total object in apparently unbounded sentences such as Lke poista+a kivu+n [medicine remove+present.3. singular pain+genitive(total)] The medicine removes the pain. This sentence can be understood as indicating either a single accomplishment where the medicine takes away someones pain, or a continuous effect of the medicine in preventing the occurrence of any pain. Although with the latter interpretation the sentence is aspectually unbounded, it can nevertheless be argued that the total object is motivated by a particular type of boundedness, namely the continuous totality of the situation, i.e. the fact that the pain is being completely prevented at each individual moment of the event. The writer also considers incremental subjects and their affect on the case marking of core arguments. The subject itself can be marked with the partitive case only in existential sentences, where the general principle is such that the partitive marks existential subjects indicating an unbounded indefinite quantity (mass noun or plural subjects). The writer demonstrates that a count noun subject can sometimes also take the partitive marking to indicate its incremental relationship with existence, i.e. its coming into existence in a gradual manner. This means that static existentials (indicating the continuous existence of an entity) and dynamic existentials (indicating that an entity is coming into existence) can be distinguished from each other: only the latter existential allows such count noun partitive subjects. For instance, the dynamic existential Tunneli+sta vyry+i nkyviin tavarajuna+a [tunnel+elative roll+past.3.singular into-view freight-train+partitive] A freight train was rolling into view from the tunnel allows the partitive whereas the static existential *Asema+lla seiso+i tavarajuna+a [station+adessive stand+past.3.singular freight-train+partitive] is impossible with a partitive subject. Transitive clauses with an incremental subject are also considered. In general, the syntactic constraint limiting the use of the partitive subject to existential clauses prohibits its use in transitive clauses, and the incremental participation of the referent of the subject can only be indicated by the case marking of the object. Thus, even when it is the referent of the subject whose incremental participation causes the progressive nature of the situation, this must be expressed by the case marking the object: Tavarajuna sivuutt+i asema+a [freight-train pass+past.3.singular station+partitive] The freight train was passing the station. Interestingly, if the quantity of the incremental subject is unbounded, the total object must be used, as in Venj+lt oste+ttu shk ylitt+ raja+n Imatra+lla [Russia+ablative buy+passive.participle electricity cross+present.3.singular border+genitive(total) Imatra+adessive] The electricity bought from Russia crosses the border at Imatra. The total object (the border) is used even though the event is unbounded and the referent of the subject (electricity) participates in it incrementally. In such examples the object marking thus represents the situation as a continuous accomplishment, even though it is not the referent of the object but of the subject that changes incrementally throughout the event. Tuomas Huumo